Interpreting "Torah" in Psalm 1 in the light of Psalm 119 - Botha, Philippus J. (HTS teologiese studies, 2012)
This article argued that Psalm 37 and Proverbs 1–4 served as sources for the composition of Psalm 1. The emphasis in both donor texts on the righteous people’s inheriting the Promised Land seems to have imprinted also on Psalm 1, a factor that could change our understanding of it. All three contexts in turn played a role in the composition of Psalm 119, but whilst the author of this long psalm also understood the ‘Torah’ of Yahweh as the incarnation of true wisdom, it seems that ‘Torah’ also subsumed the Promised Land for him. The investigation showed that ‘Torah’ in Psalm 1 should be understood as an arch-lexeme for all the religious texts its author used to compose, similar to what was the understanding of the author of Psalm 119 a little later.